2018
DOI: 10.3390/md16020046
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of Lipophilic Phycotoxins: Exposure Data and Toxicological Assessment

Abstract: Lipophilic phycotoxins are secondary metabolites produced by phytoplanktonic species. They accumulate in filter-feeding shellfish and can cause human intoxication. Regulatory limits have been set for individual toxins, and the toxicological features are well characterized for some of them. However, phycotoxin contamination is often a co-exposure phenomenon, and toxicological data regarding mixtures effects are very scarce. Moreover, the type and occurrence of phycotoxins can greatly vary from one region to ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…Thus, for a 60 kg adult to avoid exceeding the ARfD of 0.8 μg PTX eq/kg b.w., a 400 g portion of shellfish should not contain more than 48 μg PTX eq corresponding to 120 μg PTX-2 eq/kg shellfish meat [ 43 ]. In Asian molluscs, several combinations of lipophilic marine toxins were reported, including OA/YTX, OA/PTX-2, YTX/OA, PTX-2/OA, PTX-2/GYM, GYM/PTX-2 [ 44 ], and also AZA-2/PTX-2 [ 45 ]. It appears that OA is the most often recorded lipophilic toxin in mixtures, as well as the predominant toxin in the mixture [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for a 60 kg adult to avoid exceeding the ARfD of 0.8 μg PTX eq/kg b.w., a 400 g portion of shellfish should not contain more than 48 μg PTX eq corresponding to 120 μg PTX-2 eq/kg shellfish meat [ 43 ]. In Asian molluscs, several combinations of lipophilic marine toxins were reported, including OA/YTX, OA/PTX-2, YTX/OA, PTX-2/OA, PTX-2/GYM, GYM/PTX-2 [ 44 ], and also AZA-2/PTX-2 [ 45 ]. It appears that OA is the most often recorded lipophilic toxin in mixtures, as well as the predominant toxin in the mixture [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Asian molluscs, several combinations of lipophilic marine toxins were reported, including OA/YTX, OA/PTX-2, YTX/OA, PTX-2/OA, PTX-2/GYM, GYM/PTX-2 [ 44 ], and also AZA-2/PTX-2 [ 45 ]. It appears that OA is the most often recorded lipophilic toxin in mixtures, as well as the predominant toxin in the mixture [ 44 ]. Toxicological studies reporting the effects of the co-association AZA-2/PTX-2 were not found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This further enlarges the resources needed to evaluate potential toxicity of these toxins, which may be reduced by knowledge of VGSC structure in combination with bioinformatic tools, though experimental data are essential to confirm computational predictions. Aside from analogues affinity and toxicity data, a growing concern arises from additive effects of co-occurring toxins [ 87 ].…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%
“…Depending on their polarity, marine toxins can be classified as hydrophilic, lipophilic, or amphiphilic [ 9 ]. The main compounds included in the lipophilic group are okadaic acid (OA) and dinophysitoxins (DTXs), pectenotoxins, yessotoxins, azaspiracids (AZAs), and cyclic imines, the last mentioned including spirolides (SPXs), pinnatoxins, pteriatoxins, and gymnodimins.…”
Section: Introductionmentioning
confidence: 99%